If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x-6+5x=-13
We move all terms to the left:
-6x-6+5x-(-13)=0
We add all the numbers together, and all the variables
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7
| 11v+58+89=180 | | 11+3p-7=6p+6 | | 5x+3-35=18x-x | | 23+3x=6(−x+2)−25 | | 1/2=5*7/2+x | | 3(–x–5)=–3x+ | | -20x-20-10x-10=30 | | 7x+13=9x+19 | | 28x-126=14(2x-9) | | −2x−(−5−4x)=−5(2x−7) | | 3x-(x+7)+2=6x-15+(-2x) | | 6=1+8n-6 | | r+41=148r= | | –6b+(–6)+4b–4=8 | | 5-4v=27 | | 11y-2=11y-2 | | 12.5x=180 | | 27+5/x=4 | | 7(v-3)=28 | | 45+0.27x=77.40 | | 7x-65x=114 | | -6+2v+1=11 | | 8x+27x-6=7(5x+10) | | (-2)-5y=11 | | 9=2z-15 | | 3h-5=h+15 | | 15x+2=x-16 | | 4(7x+9)=64 | | 2(2x+18)=23-x | | 37x+86=37x+22 | | x-15°=2x | | 3x+6x-12-6=18 |